P35 Improving team competencies in the management of critically ill children. (5th November 2017) - Laird, A; Lawson, S; Morrow, M; Terris, M
Abstract : Background: There is increasing recognition that trainees should 'engage in simulator-based learning', 2. In 2016 a joint anaesthetic and paediatric trainee simulation course was piloted with the aim of enhancing multi-professional team-working and improving the management of critically ill children. The course consists of intermediate trainees from both paediatrics and anaesthetics with scenarios ranging from the neonate to the older child. It takes place in a high fidelity simulation suite using 'Sim Baby' and 'Sim Junior'. A paediatric trainee commences the scenario and calls for help from an anaesthetic colleague when required. Psychological fidelity is maintained by providing a 'parent' and ensuring the availability of relevant equipment e.g., drugs. Trainees observed the scenario via video link and actively participated in the debrief with faculty from both paediatric anaesthesia and paediatrics. During the pilot debrief occurred using a variety of methods which encouraged two-way communication and guidelines and papers on management were available. Overall the pilot course was a great success with feedback including "Excellent course – the combination of anaesthetics and paediatrics made this one of the most realistic scenario courses I have ever completed". Methods: Using PDSA methodology we made changes for the second course. Following feedback from the pilot, an anaesthetic nurse was invited to the faculty, increasing realism for the anaesthetic trainees. Within Northern Ireland there has been a move towards debriefing using a constructive alignment approach based on the Scottish Centre for Simulation and Clinical Human Factors Model. Utilising this debriefing model allowed the technical and non-technical learning outcomes to be better defined and discussed with the trainees. Results: The course was rewarding and trainees felt that it met their personal learning objectives. Comments were extremely positive, "Excellent course, faculty were extremely knowledgeable and helpful". One suggestion for improvement was a specific communication scenario and this will be developed for the next course. Discussion and Conclusion: Stabilising the critically ill child is a stressful and time-critical situation and it is important that these teams function effectively. Unfortunately, apart from these demanding occasions, it is rare that different specialties are afforded the opportunity to work together. This high fidelity course encourages trainees to train together, gain confidence and know when to call for senior help including our regional paediatric retrieval team. This has become an annual course that we continue to develop to improve the multi-professional management of critically ill children in Northern Ireland.